Exploring the contributions of cross-sector collaborations to Disaster Risk Reduction in the city of Harare: an investigation through a drought response lens - Nyamakura, Balbina Kudzai (Department of Environmental and Geographical Science, 2022)
The Sendai Framework for Disaster Risk Reduction calls for collaboration across sectors in society as an effective way to reduce disaster risk in order to safeguard lives, human wellbeing, and development gains from potential disasters. However, the effectiveness of these cross-sector collaboration approaches has most often been studied in the context of rapid onset disasters such as floods, with less focus on slow-onset disasters such as multiple year droughts. There is also limited research on the contributions of cross-sector collaborations towards Disaster Risk Reduction in African cities. For this study, I set out to investigate cross-sector collaboration efforts contributing to drought response in the city of Harare, Zimbabwe; and how these collaborations were contributing towards fulfilling the four priority areas of the Sendai Framework. These include i) understanding disaster risk, ii) strengthening disaster risk governance, iii) investing in disaster risk reduction for resilience, and iv) enhancing disaster preparedness for effective response. In this qualitative study, I made use of purposive and snowball sampling methods to select 14 key informants from national and local government, non-governmental organisations, and civil society organisations who were directly involved in eight drought related cross-sector collaborations. I conducted in depth semi-structured interviews with these key informants between 2018 and 2019. For the analysis, I followed prior developed themes based on Bryson et al. (2006) theoretical framework to understand cross-sector collaborations. I also applied a typology of barriers and enablers developed from the literature in the analysis, and interpreted emergent themes using NVivo software. I then assessed the contributions of the identified cross-sector collaborations to the activities listed under each of the four priority areas in the Sendai Framework. The findings highlighted the socio-political and economic context of the city of Harare had seeped through and influenced the cross-sector collaborations responding to drought. They shed light on how taking advantage of widely accessible social media platforms serve to enhance collaborations. Additionally, the results highlight the importance of existing networks and relationships in enabling cross-sector collaborations to occur effectively. Most of the cross-sector collaborations occurring in response to drought were originally formed for other reasons and included drought response during the peak of the drought disaster. Collaborations were effective at contributing towards engaging communities in risk assessment and reporting at the local level (Priority 1) and ensuring continual provisioning of services (water) during and after disasters (Priority 4). I make suggestions for collaborations to consider issues of power and how these affect the effectiveness of collaborations on the ground with regards to ensuring social justice and reducing inequality. Finally, I conclude that cross-sector collaborations would be more effective in response to slow-onset disasters when they are formed and applied before the disaster is at its peak. I also suggest that the design and implementation of the cross-sector collaborations be tailor made to consider the socio-political and economic aspects of the city in their design for effective response.